Magnetic resonance imaging‐derived proton density fat fraction (MRI‐PDFF) is a viable alternative to liver biopsy for steatosis quantification in living liver donor transplantation. Issue 7 (19th May 2021) - Qi, Qiaochu; Weinstock, Allison K.; Chupetlovska, Kalina; Borhani, Amir A.; Jorgensen, Dana R.; Furlan, Alessandro; Behari, Jaideep; Molinari, Michele; Ganesh, Swaytha; Humar, Abhinav; Duarte‐Rojo, Andres
Abstract: This study aimed to investigate whether magnetic resonance imaging‐derived proton density fat fraction (MRI‐PDFF) can be a viable noninvasive alternative to liver biopsy for the quantification of living liver donor steatosis. Hepatic steatosis for 143 donors was graded by MRI‐PDFF. Study endpoints included liver volume regeneration in donors, recipient outcomes including length of hospital stay, deaths, primary non‐function (PNF), early allograft dysfunction (EAD), and small for size syndrome (SFSS). Correlation between MRI‐PDFF determined donor steatosis and endpoints were analyzed. Donors had lower steatosis grade than non‐donors. Donor remnant liver regenerated to an average of 82% of pre‐donation volume by 101 ± 24 days with no complications. There was no correlation between percent liver regeneration and steatosis severity. Among recipients, 4 underwent redo‐transplantation and 6 died, with no association with degree of steatosis. 52 recipients (36%) fulfilled criteria for EAD (driven by INR), with no difference in hepatic steatosis between groups. MRI‐PDFF reliably predicted donor outcomes. Living donors with no or mild steatosis based on MRI‐PDFF (ie, <20%) and meeting other criteria for donation can expect favorable post‐surgical outcomes, including liver regeneration. Recipients had a low rate of death or retransplantation with no association between mild hepatic steatosis and EAD.